Predictors of readmission for postpartum preeclampsia. (3rd July 2021) - McLaren, Rodney A.; Magenta, Melissa; Gilroy, Laura; Duarte, Maria Gabriela; Narayanamoorthy, Sujatha; Weedon, Jeremy; Minkoff, Howard
ABSTRACT: Objective : To develop a predictive model for re-admission for postpartum preeclampsia (PPEC). Methods : A case-control study; cases were patients re-admitted for PPEC; controls were not re-admitted. Mixed linear modelling was used to develop a predictive model on the training set, then validated on the validation set. Results : Two-hundred-sixty-nine patients were readmitted, and matched to 538 controls. A risk calculator was developed and yielded a sensitivity and specificity for readmission of 80.9% and 53.5%, respectively. Conclusion : A predictive model using age, race, discharge blood pressures, and preeclampsia was able to predict re-admission for PPEC with a high level of sensitivity.